Pengaruh Green Marketing terhadap Keberlanjutan Lingkungan, Profitabilitas Perusahaan dan Ekonomi Masyarakat Lokal - Yudi Setiaji (Sekolah Tinggi Pariwisata AMPTA Yogyakarta, 2014)
Issues and awareness of resource conservation and the environment must be able to motivate companies to compete in the marketplace. Conservation and environmental sustainability issues should force companies to adapt the strategic planning process at a new socioeconomic need. Ecological considerations are relevant variables to achieve economic objectives through strategic green marketing concept (GMS) in the tourism business in a sustainable manner. In order to focus the development of green tourism is significant, it is the responsibility of the environment should be part of the agenda of the company, as well as an increased concern for environmental damage should be the concern of travellers, government and non-governmental organizations with a way to put pressure on the industry to have a framework that is environmentally responsible, establish codes of conduct, certification, ecolabelling, awards, and an alliance of green products. Green Marketing Strategic significant effect and can improve the quality of the environment, corporate profitability and economic growth of local communities. Personal values take effect in the company and can significantly improve the quality of the environment, corporate profitability and economic growth of local communities.Environmental values and significantly influential organizations can improve the quality of the human environment, corporate profitability and economic growth of local communities. The role of government can have a significant effect and improve the quality of the environment, corporate profitability and economic growth of local communities.